Treatment of dermatosis papulosa nigra with a 1064 nm Nd: YAG laser in dark skin with a 1-year follow-up. Issue 3 (September 2015) - Badawi, Ashraf; Al Ali, Fayza; Tome, Mohamed; Samy, Nevien
Abstract : Background: Dermatosis papulosa nigra (DPN) is a benign cutaneous condition characterized by multiple, small, hyperpigmented macular and papular lesions on the face and neck of darker skinned populations. Effective treatments such as curettage and cryotherapy are aggressive and usually associated with hypopigmentation and hyperpigmentation, scarring, and keloid formation. Objective: To evaluate the efficacy and safety of a long-pulsed 1064 nm Nd:YAG laser in the treatment of DPN. Patients and methods: Sixty patients, clinically diagnosed with DPN, of skin type IV–VI, were included in this study. They all received two treatment sessions, 3 weeks apart, using a long-pulsed 1064 nm Nd-YAG laser with a fluence ranging between 100 and 120 J/cm 2, 3 mm spot size, and two stacking pulses of 20 ms pulse duration. Laser pulses were accompanied by air cooling of the skin. Patients were followed up at 3 and 12 months after the second session. Side effects and recurrence, if any, were reported. Blinded photographic assessment was performed by three independent dermatologists who were asked to determine the degree of improvement, which was graded using a five-point scale: −1=adverse effects (pigmentary changes, textural changes or scarring), 0=no improvement, 1=mild improvement, 2=moderate improvement, and 3=complete clearance. Patient self-assessment was also performed. Results: More than 75% improvement in the size and number of the treated lesions was reported by the patients and reviewers, which was maintained until the end of the follow-up period at 12 months, with no side effects. There was a statistically significant difference in the number of lesions before the treatment and after one laser session and also between after only one session and after the second laser session. Conclusion: Long-pulsed Nd-YAG laser has proven to be a promising alternative safe treatment modality for DPN. Two sessions are recommended for the optimum clearance of the lesions.